2021
DOI: 10.36660/ijcs.20200270
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Myocardial Infarction: Effects of the “Hiperdia” and “Mais Médicos” Programs on the Hospitalizations Trends in Brazil

Abstract: Background: Stroke and acute myocardial infarction (AMI) are cardiovascular diseases commonly characterized by the development of atheromatous plaques associated with major complications and high mortality rates.Objective: To identify an epidemiological trend in hospitalizations due to stroke and AMI and to analyze the relationship between health programs applied in Primary Health Care, gender and the Federative Unit.Methods: Ecological study with a time series design between 1998 and 2018, collecting data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
5
0
5
Order By: Relevance
“…However, this was an organizational flow and capacitation program, which may have limited its ability to demonstrate an impact on the outcomes during the study period. 8 Finally, the findings reported by Santos et al should encourage the development and expansion of primary health care programs in the country, mainly in more vulnerable areas. Promoting an equal access to healthcare should be considered an essential condition for cardiovascular risk reduction and occur in parallel with measurements aimed at improving quality of life and reducing social disparities.…”
Section: Mailing Address: Paolo Blanco Villelamentioning
confidence: 88%
See 3 more Smart Citations
“…However, this was an organizational flow and capacitation program, which may have limited its ability to demonstrate an impact on the outcomes during the study period. 8 Finally, the findings reported by Santos et al should encourage the development and expansion of primary health care programs in the country, mainly in more vulnerable areas. Promoting an equal access to healthcare should be considered an essential condition for cardiovascular risk reduction and occur in parallel with measurements aimed at improving quality of life and reducing social disparities.…”
Section: Mailing Address: Paolo Blanco Villelamentioning
confidence: 88%
“…On the other hand, the hospitalizations for stroke decreased in all federated states, except for Amazonas and Roraima. 8 The authors also showed that the "Mais Médicos" program, and specially the "Hiperdia" program contributed to the reduction in hospitalizations for stroke. However, although the same effect was not observed on the rate of hospitalizations for acute myocardial infarction, these programs attenuated the progression in the number of cases.…”
Section: Mailing Address: Paolo Blanco Villelamentioning
confidence: 99%
See 2 more Smart Citations
“…Em divergência ao aumento de internações, alguns estudos que ocorreram dentro ou próximo ao intervalo de tempo analisado, indicam que o número de internações no país reduziu, como Santos et al (6) , que relatou redução das internações por AVC de 1998 a 2018. Além desse estudo, Lopes, JM et al (7) observou, de 1998 a 2012, queda nas internações por AVC isquêmico a partir de 2002 (uma redução de 73,64% de 1998 a 2005), ano da implantação do programa Hiperdia.…”
Section: Discussionunclassified